Children's Discomfort during Noninvasive Cardiac Output Monitoring by Suprasternal Ultrasonographic Transducer. Issue 1 (January 2013) - Chan, SSW; Cattermole, GN; Leung, MPY; Ho, GYL; Graham, CA; Rainer, TH
Objectives: To investigate the level of discomfort/pain in children receiving Ultrasonic Cardiac Output Monitoring (USCOM), as compared to blood pressure measurement. Methods: Healthy children, aged 3-12 years old, were recruited from kindergartens and schools as a part of the "Healthy children's vital signs and USCOM values" project. Oscillometric blood pressure was measured, followed by USCOM measurement. The discomfort experienced by the child during each intervention was assessed using the Wong-Baker FACES pain rating scale. The pain scores (scale from 0-5) were compared using Wilcoxon signed rank test. A difference in score of one point was considered to be clinically relevant. Gender differences in pain score were analysed using Mann-Whitney-U test. Results: A total of 254 subjects (131 boys, 123 girls) were included. Mean age was 7.9 years with standard deviation (SD) of 2.4 years. The median pain score for USCOM measurement was 1.0 (95% CI=1.0 to 2.0) with interquartile range 1.0 to 2.0. The median pain score for BP measurement was 1.0 (95% CI, =1.0 to 1.0) with interquartile range 0.0 to 2.0. Overall, the pain score associated with USCOM was significantly higher than that associated with BP measurement. However, the difference fails to reach the minimum clinically significant difference of one-point. No significant difference was shown between boys and girls. Conclusion: USCOM appears to be tolerated well by healthy children. The discomfort reported during USCOM measurement is comparable to that associated with blood pressure measurements.